Development of a condition- specific quality of life measure for patients with dentofacial deformity: I. Reliability of the instrument - Cunningham SJ, Garratt AM, Hunt NP (Blackwell Synergy, 2000)
The assessment of quality of life is becoming increasingly important in clinical research. Its importance in dentistry has been realised only relatively recently. Health-related quality of life is concerned with the aspects of quality of life that relate specifically to an individual’s health. This may be measured using two groups of instruments: (i) generic measures, which provide a summary of health-related quality of life and sometimes generate a single index measure of health or (ii) condition-specific measures, which focus on a particular condition, disease, population or problem and are potentially more responsive to small, but Key words: health related quality of life; clinically important, changes in health.